Analisis Koreksi Fiskal Dan Perhitungan Pajak Penghasilan Badan PT XYZ Tahun 2017 - Vionnanova, Purnamawati Helen Widjaja (Jurnal Paradigma Akuntansi, 2019)
The object used in this research is the financial report XYZ company. This research aims to know if the fiscal corrections, calculation of corporate income tax, and the tax installments of article 25 for the next year period done by the corporation match the law that operates in Indonesia; especially the law of the Republic of Indonesia No. 36 of 2008. This research use’s a descriptive method, but the data used in this research uses primary data gathered through observation, interviews, and documentation, which will be analyzed. The result shows that the fiscal corrections, and the calculation of corporate income tax done by the corporation matches with the law. However, a difference was found on the calculations of the tax installments of article 25 for the next year period. These differences could happen because there are some mistakes done in the process of adding fiscal revenue minus non-regular revenue added with non-regular expenses and calculation of gross circulation for the following year